Nerve Function Examination as a Screening for Prevention of Disability in Morbus Hansen at Kelet General Hospital, Central Java: A Case Report - Prihastomo, Teguh; Wahyu Tri Sudaryanto (HM Publisher, 2022)
Disability in leprosy or Morbus Hansen can be prevented by early diagnosis and regular and accurate treatment with multi-drug treatment. This study aimed to describe the examination of nerve function in preventing leprosy disability. In this case, a man, 21 years old, has a history of diagnosis of Morbus Hansen multibacillary type since five years ago. There are deformities in both hands and feet with red bumps. On neurological examination, there was anesthesia in hand with paralysis of the finger muscles causing claw hand. No reduction in muscle mass was seen. The patient found it difficult to move his left hand, especially on the 4th and 5th fingers. The range of motion (ROM) of the 4th and 5th fingers was limited. Examination of nerve function begins by palpating the auricular magnus, radial, ulnar, peroneus communis, and posterior tibial nerves. Motor and sensory examinations were carried out by examining the strength of the facial muscles, finger muscles, and wrist muscles. For the lower limbs, examine the muscles of the ankles and toes. In conclusion, early examination of disability and exercise therapy can help prevent disability and keep the condition of disability from getting worse.